George: thanx man, i can't believe i didn't realize what i was doing wrong..]]>

t^a/t^b=t^a-b and 1/t^a=t^-a

]]>i have a problem with integrals of trig functions.

let me explain on an example...

∫ ((Cos^3)x/Sinx^1/2)dx...

i get to the point where i use the substitution method.... Sinx=t--->cosxdx=dt

when i include this into my function i get this.... ∫ ((1-t^2)/t^1/2)dt...

i don't get the next part of the procedure... ---> ∫(t^-1/2)dt - **∫(t^3/2)dt**....

this last part i don't understand...

**i don't understand how they get the t^3/2...explanation please**

btw i know the stuff such as (cos^2)x=1-(sin^2)x and that so that i understand

]]>